VD_FINDINFO Décision / 2010 / 5 vom 6. Januar 2010 - VD Tribunal cantonal (2010)
PROCÈS DEVENU SANS OBJET, RADIATION DU RÔLE, DROIT D'OBTENIR UNE DÉCISION | 56 al. 2 LPGA, 59 LPGA, 61 let. g LPGA, 91 LPA-VD, 94 al. 1 let. c LPA-VD, 99 LPA-VD